Processing of sea gravity data using on-line navigational information of icebreaker SHIRASE - Segawa, Jiro; Kaminuma, Katsutada; Fukuda, Yoichi (1986)
P(論文) The NIPRORI-1 gravimeter of icebreaker SHIRASE was modified so that the ship's navigational data were used in real time. Examples of measurement using the modified system during the 27th Japanese Antarctic Research Expedition are given to show the performance. departmental bulletin paper